PENGARUH ATRIBUT PRODUK, BAURAN PROMOSI DAN HARGA INDOMIE DAN MIE SEDAAP TERHADAP LOYALITAS KONSUMEN INDOMIE - Istiharini . (Center for Economic Studies Universitas Katolik Parahyangan, 2006)
Indofood with lndomie as its brand is the market leader for Indonesian instant noodle. Indomie has been the market leader for instant noodle for the past thirty years. In the beginning of 2003, April 2003 to be exact, WingsFood enter the instant noodle market with Mie Sedaap for its brand. Mie Sedaap imitates lndomie's flavour, packaging color, yet with a slight difference in price. Mie Sedaap is cheaper than lndomie. Mie Sedaap existence threat lndomie. Indofood and WingsFood as the producer compete on product attributes, promotion mix and price to attract consumer to buy. Mie Sedaap new offerings attract consumer, they began to try Mie Sedaap. After trying Mie Sedaap, some of them still loyal to lndomie, some of them consume Indomie and Mie Sedaap and the others like Mie Sedaap and switch buying Mie Sedaap. We can see a declining in Indomie's loyalty.